2018
DOI: 10.1186/s13104-018-3831-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two strategies for debriefing simulation in the development of skills for neonatal resuscitation: a randomized clinical trial

Abstract: ObjectiveTo evaluate two debriefing strategies for the development of neonatal resuscitation skills in health professionals responsible for the critical newborn care in a high-complexity university Hospital.ResultsA simple blind randomized clinical trial was conducted. Twenty-four professionals (pediatricians, nurses, and respiratory therapists) were randomly assigned for two interventions; one group received oral debriefing and the other oral debriefing assisted by video. Three standardized clinical scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 16 publications
1
26
0
3
Order By: Relevance
“…The importance of constructive debriefing cannot be underestimated. Both oral debriefing and use of a video are effective (77). Video debriefing can be beneficial as part of the NRP and has been found to improve teamwork (78).…”
Section: Teaching Non-technical Skillsmentioning
confidence: 99%
“…The importance of constructive debriefing cannot be underestimated. Both oral debriefing and use of a video are effective (77). Video debriefing can be beneficial as part of the NRP and has been found to improve teamwork (78).…”
Section: Teaching Non-technical Skillsmentioning
confidence: 99%
“…Scientific production about the VAD technique, specifically about its elements, was considered incipient for this research. It may be contradictory to view the current literary collection on the VAD technique and to affirm that there are few studies in this scope, however, the number of studies that aim to describe the components that, in fact, make this technique feasible is scarce (6,20,23) , which justifies the small sample of this research.…”
Section: Discussionmentioning
confidence: 91%
“…The quasi-experimental studies identified demonstrated that the VAD technique is effective for the development of clinical skills in nursing (21)(22) . The only experimental study that compared the oral debriefing technique and the video technique, describing its elements and procedure, did not show statistically significant results, concluding that there is no superiority of one over the other (20) .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations